Picosecond Dynamics of Dimer Formation in a Pyrene Labeled Polymer - Catherine De Castro (The Journal of Physical Chemistry B, 2010)
A commercial poly(acrylic acid) (PAA, Mn = 450 000 g mol−1) has been labeled with high levels (9.1 mol %) of pyrene by reaction with 1-pyrenylmethylamine in the presence of boric acid. The modified polymer was found to display an unusual photophysical behavior closely resembling that found for pyrene in constrained environments. The appearance of a band at longer wavelengths in the excitation spectra when collected at the long wavelength emission band was attributed to the spectra of a dimer. The emission of this dimer was particularly enhanced in dioxane:water solvent mixtures with low dioxane content. From time-resolved fluorescence measurements in the picosecond time domain, two decay components were obtained: a fast decay (4−10 ps) at short wavelengths, which becomes a rising component at longer wavelengths, and a second exponential (2−4 ns) related to the emission of the relaxed dimer. Time-resolved emission spectra were seen to change with time, revealing the emission contribution of two species. This is one of the first reports where the dynamics of dimer formation in a pyrene derivative have been observed.